Pengaruh Pendampingan Suami terhadap Tingkat Kecemasan Ibu Bersalin Kala I - Istigfarah; Fibrianti; Suhaemi (STIKes Hamzar, 2024)
Anxiety, worry, and a lack of confidence are some of the abilities to give birth among the many issues that mothers experiencing labour face throughout the early stage of labour. Present a birth partner, namely the husband, to help minimize anxiety and fear during the childbirth process. The presence of a birth partner can bring comfort and peace of mind during childbirth. The goal is to investigate the influence of a husband's assistance on the level of anxiety of mothers during the first stage of delivery in the working area of Pringgasela Health Centre in 2023. This analytical observational study with a cross-sectional design was conducted in November–December 2023. The sampling technique employed was the accidental sampling of 16 respondents from mothers in the first stage of the latent phase.The data were gathered utilizing observation sheets for husbands' assistance and the Hamiton Anxiety Rating Scale (HARS) questionnaire to assess anxiety levels. The data was analyzed using the chi-squared test. Most husbands-assisted mothers in the first stage of labour were 10 persons (62.5%), while most mothers in the first stage of labour had acute anxiety, as many as 5 persons (31.2%). The analysis chi-square has a p-value <0.05, indicating that husband assistance affects mothers' anxiety levels during the initial delivery stage in the Pringgasela Health Centre operating region 2023. Husband assistance influences the level of maternal anxiety in stage 1